2022
DOI: 10.1111/jocd.15126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low‐fluence 1064 nm Q‐switched Nd: YAG laser for the treatment of melasma: A meta‐analysis and systematic review

Abstract: Background: Melasma is considered as a type of acquired facial pigmentary disorder that is challenging to treat. Low-fluence 1064 nm Q-switched Nd: YAG laser (LQSNY) has clinical benefits against melasma; however, there are some disputes.Objective: To explore these contentious views, we conducted a meta-analysis and systematic review to evaluate the efficacy and safety of LQSNY monotherapy and combined therapy for the treatment of melasma. Methods:The PubMed, Embase, Cochrane Library, and Web of Science databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Several clinical trials have been conducted to examine the use of various lasers in the management of melasma. 11,[13][14][15] However, it is difficult to reach any conclusions because of varying study designs, including different skin types, melasma types, and a range of devices and parameters. 5 The use of low-fluence QSNYL for melasma has been referred to as "laser toning" in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have been conducted to examine the use of various lasers in the management of melasma. 11,[13][14][15] However, it is difficult to reach any conclusions because of varying study designs, including different skin types, melasma types, and a range of devices and parameters. 5 The use of low-fluence QSNYL for melasma has been referred to as "laser toning" in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Some studies have evaluated the performance of QSNYL compared to other lasers for melasma treatment, but most studies have assessed the adjuvant role of laser treatment and the follow-up period was rather limited. 11 To directly compare the treatment outcomes using different lasers, we conducted this study to compare the effects of QSNYL alone versus PSAL with DLA alone for melasma with a longer-term follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the using the laser to treat chronic hyperpigmentation diseases like chloasma and post-inflammatory hyperpigmentation (PIH) shows significant benefits. 25 1064 nm QSNY can precisely target melanin phages of lesion and destroy the melanin particles within lesional melanin phages. 26 Compared to short wavelength laser (523 nm), the selected long wavelength laser (1064 nm) can be easier to pass through the epidermis to the dermis.…”
Section: Laser Therapymentioning
confidence: 99%
“…The number of laser‐related treatment modalities and combinations is increasing, but determining which combination will yield the best clinical results remains a problem. Several meta‐analyses of different laser treatments have been performed, but no multiple treatment comparison or network meta‐analysis has been conducted 14,15 . Thus, to confirm the most proper laser‐related treatment for melasma, we conducted a systematic review and NMA based on the most recently published studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses of different laser treatments have been performed, but no multiple treatment comparison or network meta-analysis has been conducted. 14,15 Thus, to confirm the most proper laser-related treatment for melasma, we conducted a systematic review and NMA based on the most recently published studies.…”
mentioning
confidence: 99%